Atherosclerotic plaque in carotid arteries in systemic lupus erythematosus: frequency and associated risk factors - Souza , Alexandre Wagner Silva de; Hatta, Francisca Satomi; Sato, Emília lnoue (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Atherosclerotic disease is an imporlant cause oi morbidity and mortality in systemic lupus erythematosus (SLE) patients. No previous studyhas estimated carotid disease prevalence in such patienls in Brazil. The aim was lo evaluale lhe prevalence oi alherosclerolic plaque in carotid arleries, in SLE palienls and conlrols, and lo verify possible associalions between risk lactors and carolid plaque. DESIGN AND SETTING: Cross-sectional sludy, at Universidade Federal de São Paulo - Escola Paulista de Medicina. METHODS: Carotid plaque prevalence was assessed by B-mode ultrasound in 82 lemale SLE palienls oi mean age 34.0 years and 62 conlrols oi mean age 35.7 years. Plaque was delined as a dislinct area oi hyperechogenicily and/or focal prolrusion oi lhe vessel wall inlo lhe lumen. Risk lactors for coronary disease and SLE-relaled variables were delermined. RESULTS: 50% oi palienls and 29% oi conlrols presenled carolid plaque. Older age, longer disease duralion, higher Syslemic Lupus lnlernalional Collaboraling Clinics (SLICC) score, higher leveis oi low-densily lipoprolein and grealer diabeles, obesily, premalure ovarian lailure and Iam ily h istory oi coronary arlery d isea se were lound in palienls wilh carolid plaque lhan in lhose wilhoul plaque. Patients with plaque were younger lhan controls with plaque. SLE diagno• sis, obesity, older age, higher SLICC score and longer disease duralion were independent risk lactors for carotid plaque. CONCLUSION: Young patients with SLE present higher prevalence oi carolid plaque lhan con rols. SLE diagnosis was a signilicanl risk lactor for carotid atherosclerosis.